Screening of media composition for bioprotein production from palm Kernel Cake by Aspergillus Niger for fish feed - Mohamad Shahemi Rasidi (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The worlds population are increasing and the demands for natural resources of food especially protein source such as fish are limited. Only a rational and sustainable effort will continue to produce enough and nutritive food, to satisfy the future needs of human kind. Bioprotein production is the one of the most promising breakthroughs of biotechnological innovation in animal feed industry, especially in fish feed. Due to its increasing demand and the high cost of other fish feed, the palm kernel cake (PKC) as a substrate was used for production of bioprotein for fulfilling fish feed industrys demand. In this project, the screening of media composition for bioprotein from production palm kernel cake by Aspergillus niger for fish feed application was carried out with different percentage value according to the Plackett-Burman design.